A methodology to predict the HPGR operational gap by using piston press tests. (1st June 2021) - Pamparana, G.; Klein, B.
Highlights: Prediction of the HPGR operational gap using piston press and pilot-scale data. A gap-calibrated methodology is proposed based on the PPT sample volume. Validations showed a high accuracy on the predictions after calibrating. Abstract: High-Pressure Grinding Rolls (HPGR) sizing requires conducting several pilot-scale tests with a large quantity of material and is costly for new projects. The University of British Columbia has developed a piston press test and models to predict the energy requirements and the size reduction capabilities for an HPGR. However, there is no small-scale test to predict either the throughput or the operational gap of the HPGR. For a given roll size, the throughput is a function of the gap between the rollers and the roll speed. This paper aims to present the concept for a novel gap-calibrated methodology that was developed to predict the operating gap by calibrating the piston press compressed bed thickness with the HPGR operational gap. On average, less than ±0.4% prediction errors have been obtained for the HPGR operating gap when validating using iron and copper ore. It is possible to predict the HPGR throughput with further calculations using the predicted gap. The proposed test and methodology are a first step towards calculating the HPGR throughput using small ore quantities.